THE IMPLEMENTATION OF THE PROJECT-BASED LEARNING MODEL TO IMPROVE LEARNING OUTCOMES ON PLANE FIGURE CONCEPTS AMONG THIRD-GRADE STUDENTS AT SD GMIM PELELOAN - Marshanda Tumarar; Roeth A.O Najoan; Deysti Trifena Tarusu (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to improve Grade III students’ mathematics learning outcomes on plane figure material through the implementation of the Project-Based Learning (PjBL) model at SD GMIM Peleloan. The novelty of this study lies in the application of PjBL to help elementary students recognize, compare, classify plane figures, and calculate the number of sides and angles through project-based activities that connect mathematical concepts with concrete learning experiences. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of two cycles. Each cycle included planning, action, observation, and reflection stages. The subjects were 8 Grade III students, consisting of 3 female and 5 male students. Data were collected through observation, tests, and documentation. The findings showed an improvement in teacher activity, student activity, and students’ learning mastery. Students’ learning outcomes increased from 60.62% in Cycle I to 92% in Cycle II. Teacher activity improved from 83.51% to 96.25%, while student activity increased from 63.81% to 95.29%. Classical learning mastery also increased from 50% in Cycle I to 87.5% in Cycle II. Therefore, the implementation of the PjBL model can improve students’ learning outcomes and promote more active, meaningful, and student-centered mathematics learning.